Pendidikan Kesehatan Pencegahan Diabetes Melitus pada Masyarakat Tanjung Anom - Pomarida Simbolon; Samfriati Sinurat; Nagoklan Simbolon (Poltekkes Kemenkes Kendari, 2021)
The incidence of Diabetes Mellitus in the community is still high, and prevention needs to be done so that people can avoid it. This community service is carried out in the context of providing health education as an effort to increase public health knowledge about diabetes mellitus prevention. The methods used are lectures and the use of audio-visual media, and pre- and post-test questionnaires are used as evaluation media. A total of 30 participants attended health education, the average achievement of the post-test questionnaire results was 2.37 points from the pre-test. There is an increase in public knowledge about DM prevention.